2019
DOI: 10.3390/en12152893
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Impact of Air Admission in a Prototype Francis Turbine at Low-Load Operation

Abstract: Due to significant changes in the energy system, hydraulic turbines are required to operate over a wide power range. In particular, older turbines which are not designed for these environments will suffer under off-design conditions. In order to evaluate whether or not such a turbine could fulfill the new requirements of the energy market, a study about the behavior of a prototype plant in low-load operation is presented. Therefore, prototype site measurements are performed to determine the most damaging opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The position and the value of the highest occurring stress at the runner depend on the respective considered operating point of the plant. In [35,40,42] it has already been shown that the highest dynamic stresses are expected near the positions of R1 and S2 in the partial load range at P/P RP = 44%. However, the simulations aimed not only to find the critical operating point but also to numerically investigate the plant's entire operating range concerning occurring stress conditions and damage effects on the runner structure.…”
Section: Guide Vanementioning
confidence: 95%
See 3 more Smart Citations
“…The position and the value of the highest occurring stress at the runner depend on the respective considered operating point of the plant. In [35,40,42] it has already been shown that the highest dynamic stresses are expected near the positions of R1 and S2 in the partial load range at P/P RP = 44%. However, the simulations aimed not only to find the critical operating point but also to numerically investigate the plant's entire operating range concerning occurring stress conditions and damage effects on the runner structure.…”
Section: Guide Vanementioning
confidence: 95%
“…For example, grid sizes of about 6 million cells were used for the investigation of transient processes in the low-load region [30] for hydropower plant 2. In the case of transient processes (e.g., STU), a mesh with approximately 13 million cells [34] was created and for the investigations of air injection and vortex shedding at the trailing edge of the runner, the existing mesh had to be refined again to approximately 37.5 million cells [35].…”
Section: Computational Fluid Dynamics (Cfd)mentioning
confidence: 99%
See 2 more Smart Citations
“…These phenomena may produce failures on the mechanical elements of the machine [44][45][46] diminishing the lifetime of the hydraulic turbines [47]. Different technical solutions have been proposed to mitigate their effects (e.g., fins [48][49][50], air injection/admission [51,52], water injection [53], air-water injection [54] and so on [55]).…”
Section: Introductionmentioning
confidence: 99%